KOMPETENSI GURU DALAM PENILAIAN PADA PEMBELAJARAN AKUNTANSI DI SMK SURAKARTA - Andani, Karina Vika; ., Sudiyanto; Muchsini, Binti (Tata Arta : Jurnal Pendidikan Akuntansi, 2016)
ABSTRACTThe objective of this research is to obtain information of teachersâ competencies of assessment in the Accounting learning at Vocational High Schools of Surakarta, which include: (1) teachersâ knowledge competencies of assessment; (2) the teachersâ attitude competencies of assessment; and (3) the teachersâ skill competencies of assessment. This research used the quantitative descriptive method with the survey approach. It was conducted at 13 Vocational High Schools of Surakarta with Accounting Expertise Com-petencies. Its population was all of the Accounting teachers as many as 53 of the schools. The samples of research consisted of 35 Accounting teachers and were determined through the proportional simple ran-dom sampling technique. The data of research were collected through test, questionnaire, and observa-tion. The test was to measure the teachersâ knowledge competencies of assessment. The questionnaire was to investigate the teachersâ attitude competencies of assessment. The observation was to investigate the teachersâ skill competencies of assessment. The data were analyzed by using the descriptive quantitative technique of analysis. The results of research are as follows. (1) The score of the teachersâ knowledge competencies of assessment in the Accounting learningis 45.1, which belongs to the less good category. The teachers with the qualification of the bachelor degree (S1) in Accounting Education and with the teaching experience of 3 â 9 years tend to have better knowledge competencies; (2) The score of the teach-ersâ attitude competencies of assessment in the Accounting learning is 72.81, which belongs to the fairly good category. The teachers with the qualification of the bachelor degree (S1) in Accounting Education and with the teaching experience of 10 â 16 years tend to have better attitude competencies; and (3) The score of the teachersâ skill competencies of assessment in the Accounting learning is 73.5, which belongs to the fairly good category. The teachers with the qualification of the bachelor degree (S1) in Accounting Education and with the teaching experience of 24 â 31 years tend to have better skill competencies.Keywords: Teachersâ Competencies, Assessment, Accounting Learning.ABSTRAKTujuan penelitian ini adalah untuk memeroleh informasi kompetensi guru dalam penilaian pada pembelajaran akuntansi di SMK Surakarta yang meliputi (1) kompetensi pengetahuan guru dalam penilaian; (2) kompetensi sikap guru dalam penilaian; dan (3) kompetensi keterampilan guru dalam penilaian. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan jenis penelitian survei. Penelitian ini dilaksanakan di 13 SMK Surakarta yang memiliki kompetensi keahlian Akuntansi. Populasi dalam penelitian ini adalah seluruh guru akuntansi di SMK Surakarta yang berjumlah 53 guru. Sampel da-lam penelitian ini berjumlah 35 guru dengan teknik pengambilan sampel proportional simple random sam-pling. Pengumpulan data menggunakan tes, angket, dan observasi. Tes digunakan untuk mengukur kompe-tensi pengetahuan guru terhadap penilaian. Angket digunakan untuk mengetahui kompetensi sikap guru terhadap penilaian. Observasi digunakan untuk mengetahui keterampilan guru dalam penilaian. Teknik analisis data menggunakan deskriptif kuantitatif. Hasil penelitian ini menunjukkan (1) kompetensi penge-tahuan guru dalam penilaian pada pembelajaran Akuntansi di SMK Surakarta sebesar 45,1 termasuk kate-gori kurang baik. Guru dengan kualifikasi pendidikan S-1 pendidikan akuntansi dengan pengalaman mengajar 3-9 tahun cenderung memiliki kompetensi pengetahuan yang lebih baik; (2) kompetensi sikap guru dalam penilaian pada pembelajaran Akuntansi di SMK Surakarta sebesar 72,81 termasuk kategori cukup baik. Guru dengan kualifikasi pendidikan S-1 pendidikan akuntansi dengan pengalaman mengajar 10-16 tahun cenderung memiliki kompetensi sikap yang lebih baik; dan (3) kompetensi keterampilan guru dalam penilaian pada pembelajaran Akuntansi di SMK Surakarta sebesar 73,5 termasuk kategori cukup baik. Guru dengan kualifikasi pendidikan S-1 pendidikan akuntansi dengan pengalaman mengajar 24-31 tahun cenderung memiliki kompetensi keterampilan yang lebih baik.Kata Kunci: Kompetensi Guru, Penilaian, Pembelajaran Akuntansi.